Land feasibility map for sewage sludge application: watershed of the Piracicaba, Capivari and Jundiaí Rivers - Brazil - Rodrigo Custódio Urban (Revista Ambiente & Água, 2016)
Considering the technical and economic characteristics of the final disposal of sewage sludge, this paper sought to develop a land feasibility map for sewage sludge (biosolids) application in the watershed of the Piracicaba, Capivari and Jundiaí (PCJ) Rivers. The PCJ watershed is located in the States of São Paulo and Minas Gerais, and is characterized by large urban areas, important industrial and agricultural areas, and steady population growth. Six restricted classes of soils to receive biosolid applications were considered. The criteria used were susceptibility to erosion, soil type, and restrictive criteria as protected areas, water courses and urban areas. The maps generated have shown that less than 30% of the soil of the PCJ watershed is suitable to biosolids application. Considering only the classes of restriction 0, 1 and 2, it was observed that the areas have great potential for biosolids application: 4,089.3 103 t TS year-1. The sugar cane crop and reforestation areas were considered a priority to receive applications among suitable areas. Suitable reforestation areas cover less than 0.15% of the area of the PCJ watershed, but can be useful for the treatment stations of the west region. The areas covered by sugar cane have an annual sewage sludge reception capacity of 2,582.7 103 t TS.